COL3A1 and MMP9 Serve as Potential Diagnostic Biomarkers of Osteoarthritis and Are Associated With Immune Cell Infiltration - Li, Shushan; Wang, Haitao; Zhang, Yi; Qiao, Renqiu; Xia, Peige; Kong, Zhiheng; Zhao, Hongbo; Yin, Li (Frontiers in Genetics, 2021)
Background: Osteoarthritis (OA), which is one of the most common age-related degenerative diseases. In recent years, some studies have shown that pathological changes occur earlier in the synovial membrane than in the cartilage in OA. However, the molecular mechanism of synovitis in the pathological process of OA has not yet been elucidated. The aim of this study was to identify novel biomarkers associated with OA and to strengthen the role of immune cells in the pathogenesis of OA. Methods: The microarray datasets were obtained from the Gene Expression Omnibus (GEO) and ArrayExpress, then analyzed by R software. The CIBERSORT deconvolution algorithm was performed to determine differential immune cell subtype infiltration. Relative expression of selected genes was assessed with qRT-PCR. In addition, western blotting was performed to evaluate protein expression level in osteoarthritic chondrocyte. Results: After analyzing the profiles from the database, we discovered 2 potential biomarkers associated with OA, including COL3A1 and MMP9, and confirmed this by qRT-PCR and Western blotting. Specifically, we found that the expression and protein levels of COL3A1 and MMP9 increased with the increase in the concentration of IL-1β. Conclusion：Our results provide valuable information and direction to explore novel targets for OA immunotherapy and diagnosis, and also help to reveal underlying biological mechanisms of OA pathogenesis.